Slab tearing and lithospheric structures in Luzon island, Philippines: constraints from P- and S-wave local earthquake tomography - Nguyen, Cong-Nghia; Huang, Bor-Shouh; Lee, Tung-Yi; Chen, Po-Fei; Nguyen, Van Duong; Narag, Ishmael; Bautista, Bartolome C.; Melosantos, Arnaldo (Frontiers in Earth Science, 2023)
Luzon Island is a complex setting of seismicity and magmatism caused by the subduction of the South China Sea lithosphere and the presence of a major strike-slip fault system, the Philippine Fault. Previous studies of the structure of this subduction zone have suggested that a ridge subduction system resulted in a slab tearing along the ridge. On the other hand, the Philippine Fault plays an important role in understanding how major strike-slip faults deform and displace at a continental scale. To constrain the lithospheric geological structure in the area and refine the slab tearing model, we performed a P- and S-wave seismic tomography travel time inversion using local earthquakes. The dataset has been combined from seismic phases reported by the International Seismological Centre and new pickings from six broadband seismic stations in northern Luzon. The three-dimensional P- and S-wave velocity models in Luzon Island were analyzed by applying the LOTOS package with a one-dimensional velocity model obtained from the VELEST program. Our tomographic images indicate contrasting velocity structures across the Philippine Fault to a depth of 60 km. Therefore, we suggest that the Philippine Fault might be a lithospheric structure that displaces both the crust and the upper mantle. The results also indicate regions of low-velocity slab windows from a depth of 40 km, which are interpreted as the sites of slab tearing. Compared with focal mechanisms and earthquake occurrence in this region, we propose that slab tearing extends from the fossil ridge and creates regional kinematic perturbations. The tearing produces shallow upwelling magma to stay in the chambers beneath the crust, which is in contrast to the magmatic system observed in other regions.